2009
DOI: 10.1038/sj.bjc.6605477
|View full text |Cite
|
Sign up to set email alerts
|

CD133+ circulating haematopoietic progenitor cells predict for response to sorafenib plus erlotinib in non-small cell lung cancer patients

Abstract: Background: Blood-based biomarkers may be particularly useful for patient selection and prediction of treatment response for angiogenesis inhibitors. Circulating endothelial cells (CECs) and haematopoietic progenitor cells (HPCs) might have a role in tumour angiogenesis and in tumour growth. Measurement of CECs and HPCs in the blood of patients could be a simple, non-invasive way to monitor or predict responses to treatment. Methods: (VEGFR2 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
(56 reference statements)
2
25
2
Order By: Relevance
“…Since CECs are rare events, their precise quantification in peripheral blood (PB) samples requires a technically rigorous analytical approach, which should take many factors into consideration (8). Several pre-analytical and analytical steps significantly affect not only the quantification of CECs, but can also result in a change in the definition of these cells, leading to problems in the interpretation of the results (Table I) and in their potential association with clinical endpoints (Table II) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Flow Cytometric Analysis Of Circulating Endothelial Cells Inmentioning
confidence: 99%
“…Since CECs are rare events, their precise quantification in peripheral blood (PB) samples requires a technically rigorous analytical approach, which should take many factors into consideration (8). Several pre-analytical and analytical steps significantly affect not only the quantification of CECs, but can also result in a change in the definition of these cells, leading to problems in the interpretation of the results (Table I) and in their potential association with clinical endpoints (Table II) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Flow Cytometric Analysis Of Circulating Endothelial Cells Inmentioning
confidence: 99%
“…Multiple phase I, II, and III trials with SO alone or in combination with other chemotherapeutic drugs are ongoing. Mechanistically, SO inhibits vascular endothelial growth factor (VEGF) receptor-2 and VEGF receptor-3 expressed by endothelial cells and CD133 + circulating hematopoietic progenitor cells (15) and platelet-derived growth factor receptor-β, FLT3, Ret, and c-Kit expressed by vasculatureassociated cells and tumor cells (16,17). These kinases are involved in tumor angiogenesis, as well as in growth and progression of a variety of tumor types such as leukemias and renal cell and hepatocellular carcinomas, suggesting CSC targeting by SO.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a biomarker analysis from a phase II trial of sorafenib plus erlotinib as first-line treatment for advanced NSCLC suggest a potential role for CD133-positive (CD133+) circulating hematopoietic progenitor cells (HPCs) for predicting response and TTP [48]. This study found that baseline levels of CD133+ HPCs were significantly lower among responders versus nonresponders (P=0.01), and values lower than the median were correlated with prolonged TTP (P=0.037).…”
Section: Multitargeted Antiangiogenic Tkismentioning
confidence: 70%
“…This study found that baseline levels of CD133+ HPCs were significantly lower among responders versus nonresponders (P=0.01), and values lower than the median were correlated with prolonged TTP (P=0.037). However, baseline CD133+ HPCs were not associated with baseline VEGF levels [48].…”
Section: Multitargeted Antiangiogenic Tkismentioning
confidence: 98%